Who is a libertarian and why do we need a libertarian party in India? - Anurag Dhaka (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2024)
There are a number of different ways to look at the social, political and economic climate prevailing at any point of time, some of the major ones would be Communism, Socialism, Liberalism, Welfarism and so on. These ideologies act as prisms through which a person would look at the world, the world as it is and the world as it should be. They are all encompassing ideologies, which means that they are not limited any particular sphere of life but cover the full spectrum. Libertarianism is another such prism to look at the world centred around the core value of freedom maximizing. The following paper attempts to describe the core tenets of libertarianism, or put another way, it aspires to chalk out who a libertarian is and at the same time make a case as to why we are in a dire need of libertarian party in a deeply socialist country.